Novel Delivery of Mitoxantrone with Hydrophobically Modified Pullulan Nanoparticles to Inhibit Bladder Cancer Cell and the Effect of Nano-drug Size on Inhibition Efficiency - Xiaojun Tao; Ting Tao; Yi Wen; Jiajin Yi; Lihua He; Zixuan Huang; Yu Nie; Xiaoyan Yao; Yingying Wang; Chunlian He; Xiaoping Yang (Nanoscale Research Letters, 2018)
Abstract Reducing the dosage of chemotherapeutic drugs via enhancing the delivery efficiency using novel nanoparticles has great potential for cancer treatment. Here, we focused on improving mitoxantrone delivery by using cholesterol-substituted pullulan polymers (CHPs) and selected a suitable nano-drug size to inhibit the growth of bladder cancer cells. We synthesized three kinds of CHPs, named CHP-1, CHP-2, CHP-3. Their chemical structures were identified by NMR, and the degree of cholesterol substitution was 6.82%, 5.78%, and 2.74%, respectively. Their diameters were 86.4, 162.30, and 222.28 nm. We tested the release rate of mitoxantrone in phosphate-buffered saline for 48 h: the release rate was 38.73%, 42.35%, and 58.89% for the three CHPs. The hydrophobic substitution degree in the polymer was associated with the self-assembly process of the nanoparticles, which affected their size and therefore drug release rate. The release of the three drug-loaded nanoparticles was significantly accelerated in acid release media. The larger the nanoparticle, the greater the drug release velocity. At 24 h, the IC50 value was 0.25 M, for the best inhibition of mitoxantrone on bladder cancer cells. 3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) experiments demonstrated that drug-loaded CHP-3 nanoparticles with the largest size were the most toxic to bladder cancer cells. Immunofluorescence and flow cytometry revealed that drug-loaded CHP-3 nanoparticles with the largest size had the strongest effect on promoting apoptosis of bladder cancer cells. Also, the three drug-loaded nanoparticles could all inhibit the migration of MB49 cells, with large-size CHP-3 nanoparticles having the most powerful inhibition.